1993
DOI: 10.1172/jci116169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of oxytocin in amnion, chorion, and decidua may influence the timing of human parturition.

Abstract: Despite the widespread clinical use of oxytocin (OT) as a potent and specific stimulant of labor, previous research data have not supported a role for OT in the physiology of normal human parturition. We have demonstrated synthesis of OT mRNA in amnion, chorion, and decidua using Northern blot analysis, ribonuclease protection assays, and in situ hybridization. Probes directed towards both the 3' and 5' ends of the gene have been used. Levels were highest in decidua with considerably less in chorion and amnion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(124 citation statements)
references
References 63 publications
5
117
1
1
Order By: Relevance
“…Interestingly, significantly greater concentrations of OT mRNA were detected in the chorio-decidua after spontaneous onset of labour (at the expulsive stage of parturition) compared to before the onset of labour at term [27][28][29]. Post labour chorio-decidua samples showed similar levels of OT mRNA to that of spontaneous labour, indicating the maximal level of gene expression.…”
Section: Previously Established Roles Of Ot/otr Systemmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, significantly greater concentrations of OT mRNA were detected in the chorio-decidua after spontaneous onset of labour (at the expulsive stage of parturition) compared to before the onset of labour at term [27][28][29]. Post labour chorio-decidua samples showed similar levels of OT mRNA to that of spontaneous labour, indicating the maximal level of gene expression.…”
Section: Previously Established Roles Of Ot/otr Systemmentioning
confidence: 92%
“…In 1993, mRNA of OT was isolated in human uterine tissues in late gestation [27]. A semi-quantification analysis revealed that OT mRNA is principally localised/or identified in decidua but also found in the chorion and amnion.…”
Section: Previously Established Roles Of Ot/otr Systemmentioning
confidence: 99%
“…This positive feedback continues till expulsion and stops after delivery of the baby in the process of normal labor. In addition, these uterine contractions are reinforced as Oxytocine stimulates prostaglandin production by the uterine lining [11,12].…”
Section: Possible Explanation Of How This Maneuver Workmentioning
confidence: 99%
“…At the periphery, AVP regulates water excretion, vascular tone, and adrenocorticotropin (ACTH) secretion (De Rouffignac et al 1991, de Keyzer et al 1996, Szczepanska-Sadowska 1996 while OT stimulates milk ejection and enhances uterine contractility during parturition (Chibbar et al 1993, Nishimori et al 1996. In the central nervous system, AVP is involved in thermoregulation, learning and memory processes, social recognition, and aggressive behavior (de Wied et al 1993, Alescio-Lautier & Soumireu-Mourat 1998, Rose & Moore 2002) while OT plays a crucial role in sexual activity and induces maternal behavior (Pedersen & Prange 1979, Ivell et al 1997.…”
Section: Introductionmentioning
confidence: 99%